APPLICATION OF PUZZLE MEDIA TOWARDS THE BEGINNING READING AND WRITING SKILLS OF CLASS II STUDENTS IN PRIMARY SCHOOL NEGERI 27 BANDA ACEH - Mauliza, Deli; Sulaiman, Sulaiman; Yamin, M. (Elementary Education Research, 2024)
Puzzle media is an educational game tool for children by disassembling and assembling. Elementary school students' initial reading and writing skills are the basic skills for subsequent reading and writing skills. Beginning reading and writing skills, especially lower classes such as classes I and II, require attention and strategies during the learning process in the form of methods or media. Puzzle media is one of the media that can help teachers in the process of learning initial reading skills. The formulation of the problem is: "How is the application of puzzle media to the initial reading and writing skills of class II students at SD Negeri 27 Banda Aceh?" As for the aim, based on the problem formulation, the author's aim in this research is to describe the application of puzzle media to the beginning reading and writing skills of class II students at SD Negeri 27 Banda Aceh. The approach in this research is to use a qualitative approach with a descriptive research type. The subjects in this research were class teachers and 34 class II-A students. Data collection techniques use observation, interviews and tests. All collected data is processed using the data analysis stage, namely data reduction, data presentation, and drawing conclusions. Based on the results of research that has been conducted, regarding the use of puzzle media on students' initial reading and writing skills in class II-A of SD Negeri 27 Banda Aceh, it can be concluded as follows: The application of puzzle media in the learning process is carried out by distributing puzzle media to students and students are directed by the teacher on how or steps to use puzzle media. In learning activities using puzzle media, there is a good increase in student activity when using puzzle media in learning to be good and very good, students become more enthusiastic and enthusiastic in learning using puzzle media.